The effectiveness of psychosocial interventions at reducing the frequency of alcohol and drug use in parents: findings of a Cochrane Review and meta‐analyses. (3rd March 2022) - McGovern, Ruth; Newham, James; Addison, Michelle; Hickman, Matt; Kaner, Eileen
Abstract: Background and aim: Parental substance use is a major public health and safeguarding concern. There have been a number of trials examining interventions targeting this risk factor. We aimed to estimate the effectiveness of psychosocial interventions at reducing parental substance use. Design: We used systematic methods to identify trials; pooling data using a random‐effects model. Moderator analyses examined influence of parent gender, presence of child in treatment and intervention type. Setting: No restrictions on setting. Participants: Substance using parents of children below the age of 21 years. Interventions: Psychosocial interventions including those that targeted drug and alcohol use only, and drug and alcohol use in combination with associated issues. Measurements: Frequency of alcohol use and frequency of drug use. Findings: We included eight unique studies with a total of 703 participants. Psychosocial interventions were more effective at reducing the frequency of parental alcohol use than comparison conditions at 6‐month [standardized mean difference (SMD) = – 0.32, 95% confidence interval (CI) = –0.51 to −0.13, P  = 0.001] and 12‐month follow‐up (SMD = –0.25, 95% CI = –0.47 to −0.03, P  = 0.02) and frequency of parental drug use at 12 months only (SMD = –0.21, 95% CI = –0.41 to −0.01, P  = 0.04). Integrated interventions which combined both parenting and substance use targeted components were effective at reducing the frequency of alcohol use (6 months: SMD = –0.56, 95% CI = –0.96 to −0.016, P  = 0.006; 12 months: SMD = –0.42, 95% CI = –0.82 to −0.03, P  = 0.04) and drug use (6 months: SMD = –0.39, 95% CI = –0.75 to −0.03, P  = 0.04; 12 months: SMD = –0.43, 95% CI = –0.80 to −0.07, P  = 0.02). Interventions targeting only substance use or parenting skills were not effective at reducing frequency of alcohol or drug use at either time‐point. Conclusion: Psychosocial interventions should target both parenting and substance use in an integrated intervention.